Business in a changing climate : explaining industry support for carbon pricing - Munroe, Kaija Belfry, 1981- (University of Toronto Press, 2016)
"Climate change skeptics and business pundits alike are convinced that any public policy instruments used to curtail environmental degradation are antithetical to the interests of the corporate community. However, many companies have actually come out in favour of carbon pricing. In Business in a Changing Climate, Kaija Belfry Munroe examines this counterintuitive action and, in doing so, explains how large firms determine their preferences for public policy options. Her analysis of thirteen industrial associations and seventeen firms from industries such as petrochemical, forestry, mining, and steel, reveals that, despite the higher costs, these industries prefer carbon pricing over voluntary agreements. Based on enlightening interviews with executives, government, and NGO officials, Belfry Munroe argues that the acceptance of climate change policy by companies is determined by the risks posed to capital investments and investor concern."--